An Analysis of Code Mixing by Zelynafah on TikTok Video - Ahmad, Inne Maura; Sudirman, Ade; Riandi, Riandi (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
This research paper aims to investigate the Analysis of Code Mixing by Zelynafah on TikTok Video. This research paper employs the qualitative research design with descriptive-qualitative method. The data collection methods in this study involved observation, documentation, and checklists. The data are obtain from 10 videos TikTok by Zelynafah. The finding showed that all data, namely Subject A1 to Subject C3, had types of Code Mixing based on Hoffman's theory, namely Intra Sentential, Intra-Lexical and Alterations but, only subject B2, C1 and C2 had Intra Lexical and Alterations. While there are only 5 out of 6 forms of Code Mixing based on Suwito’s theory, there are Word Insertion of Code Mixing, Phrase Insertion of Code Mixing, Hybrid Insertion of Code Mixing, Repetition Insertion of Code Mixing and Idiom Insertion of Code Mixing. In this research, Bilingualism such as Code Mixing was phenomenon mixed of two language in one utterance. The Code Mixing happens is that in beginning, middle or end of utterance. This finding also expects other researchers to further analyze Sociolinguistics so as to maximize explore other types and forms of Code Mixing in complete